Effectiveness of a Multimodal Treatment Program for Somatoform Pain Disorder. Issue 3 (4th December 2013) - Pieh, Christoph; Neumeier, Susanne; Loew, Thomas; Altmeppen, Jürgen; Angerer, Michael; Busch, Volker; Lahmann, Claas
Abstract Chronic pain conditions are highly prevalent, with somatoform pain disorder accounting for a large proportion. However, the psychological forms of treatment currently used achieve only small to medium effect sizes. This retrospective study investigated the effectiveness of a 5‐week multimodal pain program for patients with somatoform pain disorder. The diagnosis of somatoform pain disorder was confirmed by a specialist for anesthesiology and pain management and a specialist for psychosomatic medicine. Therapy outcome was evaluated with a Numeric Rating Scale (NRS), the Pain Disability Index (PDI), and the Pain Perception Scale. Within the study sample (n = 100), all parameters showed a significant and clinically relevant improvement at the end of therapy (P values < 0.001). The highest effect sizes (d) were found for reduction in average pain rating (NRS: d = 1.00) and the affective items of the Pain Perception Scale (SES‐A: d = 0.07). The lowest effect sizes were found for improvement of pain‐related disabilities (PDI: d = 0.42) and sensory items of the Pain Perception Scale (SES‐S: d = 0.50). Despite high chronification of pain condition, with average pain duration of greater than 8 years, the multimodal treatment program showed medium to large effect sizes on the outcome of patients with somatoform pain disorder. Compared with previous data with small to moderate effect sizes, a multimodal program seems to be more effective than other interventions to address somatoform pain disorder.